Reconceptualizing livestock waste as an energy resource: The role of biogas systems in achieving circular and low-carbon economies - Kette, Arlindo Umbu Saki; Susiolo, Bambang; Suhartini, Sri; Setyawan, Hendrix Yulis (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Energy is an important factor supporting the fulfillment of human life needs and the economy in both developed and developing countries, including Indonesia. One energy source that has potential for development and implementation in Indonesia is biomass. Livestock manure is one of the biomasses available in Indonesia that contains methane gas which can be used as a biogas energy source. Initial substrate characterization is very important for understanding the potential and efficiency of anaerobic fermentation processes in biogas production. Cattle manure as lignocellulose biomass has physical and chemical properties that affect the rate of organic degradation and methane yield. The CHNSO test method uses CHNSO Elemental analyzer, Hemicellulose test uses the Chesson method, Total N test uses the Kjeldahl method, P and K methods follow SNI 7763: 2018. Research results showed C 41.27%, H 4.63%, N 0.954%, S n. a, O 18.01%, N-Total 1.365, P₂O₅ 0.797, K₂O 0.594, Hemicellulose 15.788, Cellulose 34.62, Lignin 29.85, Lignocellulose 80.26, Dry Matter 93.97, Ash Content 18.26, Crude Protein 7.43, Crude Fiber 35.85, Crude Fat 0.28, Methane Yield Content 109.80. Cattle manure has high lignocellulose content and optimal C/N ratio with methane yield of 109.80 mL/g VS, demonstrating potential as a renewable energy substrate as well as raw material for organic fertilizer rich in macro nutrients.